2020
DOI: 10.1007/978-3-030-47426-3_57
|View full text |Cite
|
Sign up to set email alerts
|

Inter-sentence and Implicit Causality Extraction from Chinese Corpus

Abstract: Automatically extracting causal relations from texts is a challenging task in Natural Language Processing (NLP). Most existing methods focus on extracting intra-sentence or explicit causality, while neglecting the causal relations that expressed implicitly or hidden in inter-sentences. In this paper, we propose Cascaded multi-Structure Neural Network (CSNN), a novel and unified model that extract intersentence or implicit causal relations from Chinese Corpus, without relying on external knowledge. The model em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 9 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…On analyzing the strength of the association between the observed disease burden and obesity-related coverage, we found that cardiovascular diseases were the most frequent disease type. In comparison, metabolic dysfunction and inflammation caused by obesity are ignored in the news, despite scientific evidence indicating that metabolic dysfunction caused by obesity contributes to a wide variety of disorders and effects on the nervous system [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On analyzing the strength of the association between the observed disease burden and obesity-related coverage, we found that cardiovascular diseases were the most frequent disease type. In comparison, metabolic dysfunction and inflammation caused by obesity are ignored in the news, despite scientific evidence indicating that metabolic dysfunction caused by obesity contributes to a wide variety of disorders and effects on the nervous system [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Causality is one of the discourse analyses performed by extracting semantic relationships between cause and consequence for learning and predicting the structure of a sentence [ 33 ]. Analyzing causality is a common practice for studying the data corpus of machine learning [ 6 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…• CSNN 15 uses CNN and self-attention to capture features relationship, and the higher-level phrase representations are feed into BiLSTM and CRF layer for CEE.…”
Section: Baseline Methodsmentioning
confidence: 99%
“…Besides, Dasgupta and Dunietz et al 12,13 apply long short-term memory (LSTM) to CEE to capture the long-term dependence of sentences. Furthermore, Ma and Jin et al 14,15 combine CNN and LSTM to take advantage of both architectures. Though neural networks have achieved state-of-the-art performance, CEE is still remains a hard problem due to its complexity and ambiguity.…”
Section: Implicit Causal Sentencementioning
confidence: 99%
“…Recently, neural-based extraction methods have become a majority of related tasks in NLP, relation classification [18], relation extraction [14] and sequence tagging [10]. Among these methods, pre-trained language models [4] (e.g., BERT) dominate the state-of-the-art results on a wide range of NLP tasks.…”
Section: Introductionmentioning
confidence: 99%